Structural features and characteristic of process of training of the sportsman as the system object - Oleg Kamayev (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to specify methodological bases of the system approach in practice of training of sportsmen. Material & Methods: the system of training of the sportsman was considered. The following methods of the research are used: theoretical analysis and synthesis of scientific-methodical information, system analysis, and structurally-functional analysis. Result: structural bases of the system of training of the sportsman, its characteristic properties, types and features of functioning of this system, types of communications between structural educations, between them and complete system of training of the sportsman are defined. Conclusions: the main methodological basis of the system approach to the process of training of the sportsman is the way of its consideration as the system object, definition of properties, characteristic of it, features of its functioning and types of communications between structural elements and in the system in general.